2017
DOI: 10.15252/embj.201695534
|View full text |Cite
|
Sign up to set email alerts
|

AKT‐phosphorylated FOXO1 suppresses ERK activation and chemoresistance by disrupting IQGAP1‐MAPK interaction

Abstract: Nuclear FOXO proteins act as tumor suppressors by transcriptionally activating genes involved in apoptosis and cell cycle arrest, and these anticancer functions are inhibited by AKT-induced phosphorylation and cytoplasmic sequestration of FOXOs. We found that, after AKT-mediated phosphorylation at serine 319, FOXO1 binds to IQGAP1, a hub for activation of the MAPK pathway, and impedes IQGAP1-dependent phosphorylation of ERK1/2 (pERK1/2). Conversely, decreased FOXO1 expression increases pERK1/2 in cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 56 publications
5
65
0
Order By: Relevance
“…Given that FOXO1 does not directly binds to the DNA binding motif of ERG, the exact mechanism by which FOXO1 interaction reduces ERG recruitment to its downstream targets is unclear. However, our data cannot rule out the possibility that FOXO1 interaction with the N-terminal half of ERG may affect ERG DNA binding by causing overall conformation changes in ERG protein as demonstrated in IQGAP1, another FOXO1 interacting protein (27). …”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Given that FOXO1 does not directly binds to the DNA binding motif of ERG, the exact mechanism by which FOXO1 interaction reduces ERG recruitment to its downstream targets is unclear. However, our data cannot rule out the possibility that FOXO1 interaction with the N-terminal half of ERG may affect ERG DNA binding by causing overall conformation changes in ERG protein as demonstrated in IQGAP1, another FOXO1 interacting protein (27). …”
Section: Resultsmentioning
confidence: 63%
“…PTEN loss leads to AKT and CDK1- or CDK2-mediated phosphorylation of FOXO1, exclusion of FOXO1 from the nucleus, and loss of the tumor suppressor functions in the nucleus (15,2224). Increasing evidence suggests that AKT-phosphorylated FOXO1 also possesses tumor suppressor functions in the cytoplasm (2527). In agreement with these findings, proteosome degradation of AKT-phosphorylated FOXO1 is critical for PI3K-AKT-mediated cell transformation and oncogenesis (2830).…”
Section: Introductionmentioning
confidence: 99%
“…2A; refs. 68, 18, 19). Similar to these findings, we demonstrated that IQGAP1 interacted with components of the MAPK pathway in PANC-1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Drug resistance is identified as a major obstacle in tumor chemotherapy, and miRNAs have been reported to serve critical roles in this process (17)(18)(19)(20)(21)(22)(23). To date, several studies have identified that miR-149 exerts a critical function in numerous types of tumors.…”
Section: Discussionmentioning
confidence: 99%